On the tensile strength of spark plasma sintered AlMgB14 ceramics - Nikitin, Pavel Yu; Zhukov, Ilya A.; Tkachev, Dmitriy; Kozulin, Alexander A.; Vorozhtsov, Alexander B. (Nanomaterials)
In this work, the structure, phase composition, hardness and tensile strength of the AlMgB14-based material obtained by spark plasma sintering (SPS) were investigated. According to the XRD results, the spark plasma sintered material contains 94 wt% AlMgB14 phase and 6 wt% spinel MgAl2O4. Analysis of the SEM images showed that the obtained AlMgB14 sample has a dense structure; the relative density of the sample is 98.6%. The average microhardness of the spark plasma sintered (SPSed) sample is 29 ± 0.88 GPa. According to the results of the Brazilian test, the tensile strength of AlMgB14 is 56 MPa. The fracture is characterized by a single straight tensile crack that divides the sample along the compression line into two halves. The type of fracture in the AlMgB14 sample can be characterized as a cleavage fracture due to crack growth occurring in accordance with the transcrystalline fracture. The tensile strength of the obtained material is in good agreement with the tensile strength of boride and oxide ceramics studied in other works.